The Sound of G: A Method to Calculate The Acceleration Due to Gravity Using Acoustic Stopwatch - Pacala, F. A.; Pili, U. (Jurnal Pendidikan Fisika Indonesia, 2023)
This paper explored to calculate the value of the acceleration due to gravity (g) by using primarily of balloons, mass hanger, an acoustic stopwatch of a smartphone. The acoustic stopwatch used is based on the PhyPhox mobile application. The independent variable was the drop height and the dependent variable is the recorded time. There were seven drop heights and time were recorded for each fall with three repetitions to reduce the error. The computed value of g was comparable to the average value of g of 9.81 m/s and the locally accepted value. The measure value of g is also similar to the findings of various literatures. This proved the ability of the application to measure the drop time with reducing random or systematic errors. The data gathered from this research has proven that simple mobile phone has now tremendous impact in the classroom experiments.  The students now can compute g more than visualizing it. The use of an acoustic stopwatch from a mobile phone in a physics experiment can be a great way for students to gain a better understanding of measuring and interpreting data accurately. The app makes it easier for teachers to demonstrate the concept of measurements and how to properly record them by using audio cues from the phone's built-in microphone.